2020
DOI: 10.1097/md.0000000000019276
|View full text |Cite
|
Sign up to set email alerts
|

Drug-eluting beads transarterial chemoembolization by CalliSpheres is effective and well tolerated in treating intrahepatic cholangiocarcinoma patients

Abstract: This study aimed to investigate the efficacy and safety of drug-eluting beads (DEB) transarterial chemoembolization (TACE) treatment in Chinese intrahepatic cholangiocarcinoma (ICC) patients. 37 ICC patients underwent DEB-TACE treatment in CTILC study (registered on clinicaltrials.gov with registry No. NCT03317483) were included in this present study. Treatment response was assessed according to modified Response Evaluation Criteria in Solid Tumors (mRECIST). Overall survival (OS) was calculated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…It is reported that DEB-TACE with Callispheres microsphere increases tumor response featured by higher ORR and CR rates compared to cTACE in HCC patients [9,10]. Regarding its clinical application in ICC patients, two single-armed retrospective studies show that the ORR rates in DEB-TACE with Callispheres microsphere treated ICC patients are 65.9% and 67.6%, respectively [12,13]. Since DEB-TACE with Callispheres microsphere displays improved efficacy and safe compared to cTACE in treating HCC patients, also DEB-TACE with Callispheres microsphere is safe and well-tolerant in ICC patients, therefore we hypothesized that DEB-TACE with Callispheres microsphere might achieve great efficacy compared to cTACE in ICC patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that DEB-TACE with Callispheres microsphere increases tumor response featured by higher ORR and CR rates compared to cTACE in HCC patients [9,10]. Regarding its clinical application in ICC patients, two single-armed retrospective studies show that the ORR rates in DEB-TACE with Callispheres microsphere treated ICC patients are 65.9% and 67.6%, respectively [12,13]. Since DEB-TACE with Callispheres microsphere displays improved efficacy and safe compared to cTACE in treating HCC patients, also DEB-TACE with Callispheres microsphere is safe and well-tolerant in ICC patients, therefore we hypothesized that DEB-TACE with Callispheres microsphere might achieve great efficacy compared to cTACE in ICC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the safety profile of DEB-TACE with Callispheres microsphere in ICC patients, one study discovers that the major adverse events of DEB-TACE with Callispheres microsphere in ICC patients are abdominal pain, fever, vomiting and nausea, which are all mild and manageable [12]. Among these, patients received DEB-TACE significantly less likely to experience abdominal pain compared to patients received cTACE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that TACE reaches satisfactory efficacy and is well tolerated in elderly patients, including those above 85 years old [ 114 , 115 ]. Recent studies have described that drug-eluting bead-TACE therapy was safe and effective in elderly patients either with HCC [ 116 ] or iCCA [ 117 ].…”
Section: Palliative Treatmentsmentioning
confidence: 99%
“…Propensity score‐matched analysis showed a significant survival benefit for patients who received chemotherapy plus DEB-TACE compared to those undergoing chemotherapy only. Recently, a prospective multicenter study including 37 patients with iCCA was conducted ( 57 ). For patients treated with DEB-TACE loaded with Adriamycin, about 8.1% of them achieved CR, while 59.5% achieved PR.…”
Section: Interventional Treatment For Ccamentioning
confidence: 99%